The level of serum Tumor Marker CA15-3 in women with Breast Cancer - Othman, Huda Hameed; Abood, Walaa Najm; Alwakeel, Nazar Abdul Hassan (Diyala Journal of Medicine, 2018)
Background: Breast cancer is the most frequently diagnosed type of cancer in women in all world regions. About 1.7 million cases of breast cancer are diagnosed every year. Breast cancer is the most common cause of death in women worldwide. There were approximately 0.5 million deaths worldwide from breast cancer in 2012, several serum tumor markers have been evaluated in breast cancer. CA15-3 is the most important serum biomarkers used for diagnosis and monitoring of breast cancer. Objective: To evaluate the level of CA15-3 of studied groups according to age categories, residence nearby industries, and history of breast feeding. Patients and Methods: This study was carried out at the Breast Surgery Outpatients and the Oncology Clinic at Oncology Teaching Hospital in Baghdad. It included 50 women who were newly diagnosed by oncology group to have had breast cancer and didn’t receive chemotherapy yet and 50 healthy women as control. Results: There was significant increase at (P> 0.05) in serum CA15-3 level of patients with age category (71-80) years (198.33 ± 136.60 U/ml) and significant elevation in serum CA15-3 level of patients who lived near industries or incinerators (120 ± 94.52 U/ml) also there was significant increase in serum CA15-3 level in healthy women with breast feeding history (25.8 ± 15.26 U/ml). Conclusion: CA15-3 level significantly elevated in elderly patients with age category (71-80) years and in patients with residence nearby industries or incinerators. Therefore, those patients at high risk of developing metastatic breast cancer or advanced stages of breast cancer.